The use of artificial intelligence programs as experienced by Generation X digital shoppers of the clothing industry - Adriano, Mardy A., Banda, Jewel Ann I., Dimaranan, Andrea S., Oria, Ma. Ellaine L., Reyes, James Andre T., Rivera, Shannen Maroe C., Vinoya, Jenilyn R. 4 0 16; 5
Abstract With the rapid growth of e-commerce and the increasing reliance on digital platforms for shopping, understanding how Al technologies could improve the overall shopping experience was crucial. This research aimed to investigate the use of artificial intelligence (Al) programs as experienced by Generation X digital shoppers in the clothing industry in Metro Manila. Employing a quantitative-correlational research approach, the study explored the overall efficiency of Al programs, including recommendation systems, chatbots, and visual search and image recognition, in relation to customer satisfaction's three key aspects: customer retention, customer referral, and customer related sales. The findings revealed a significant relationship between the level of familiarity with Al programs and the level of experienced efficiency among Generation X. This research contributed valuable insights into Al programs' potential to enhance the digital shopping experience and offered implications for businesses and marketers targeting the Filipino Generation X market. Keywords: Artificial Intelligence (Al), E-commerce, Generation X, Digital Shopping Experience
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2